Organizational Innovation in Times of Crises: The Case of Extension and Advisory Services - Krisin Davis; Anna Snider; Thomas Archibald; Benjamin Grove; Suresh Babu (Journal of International Agricultural and Extension Education, 2021)
Since it formally began, extension institutions have been innovating in response to the changing environment. Past crises have induced organizational innovation in limited ways. The COVID-19 crisis appears to have brought about more radical change in extension organizations. In this manuscript, we apply organizational change theory—including insights from recent research on adaptive management in international development—to examine how extension organizations innovated during the COVID-19 crisis. We explore how extension organizations modified inputs such as human capital, technology, and equipment; outputs such as services; and organizational components, such as social structures, participants, and goals. We review previous crises to learn how global extension adapted and then examine contemporary experiences of organizational change during COVID-19. This allows us to provide suggestions for future directions for implementers on how to strengthen extension services to respond in times of crisis and continue to support clientele in varying circumstances. We suggest that extension organizations embrace inclusive technology cautiously, provide staff with skills to adapt and problem solve, and ensure flexible structures that allow for collaboration.
Keywords: extension; innovation; managing change; organizations